Growth of spiral ganglion neurons induced by graphene oxide/oxidized bacterial cellulose composite hydrogel. (1st July 2023) - Shi, Lin; Hong, Guodong; Chen, Chuntao; Li, Xueqian; Zhang, Heng; Chai, Renjie; Sun, Dongping
Abstract: The damage or degeneration of spiral ganglion neurons (SGNs) can impair the auditory signals transduction from hair cells to the central auditory system, and cause significant hearing loss. Herein, a new form of bioactive hydrogel incorporating topological graphene oxide (GO) and TEMPO-oxidized bacterial cellulose (GO/TOBC hydrogel) was developed to provide a favorable microenvironment for SGN neurite outgrowth. As the network structure of lamellar interspersed fiber cross-linked by GO/TOBC hydrogels well simulated the structure and morphology of ECM, with the controllable hydrophilic property and appropriate Young's modulus well met those requirements of SGNs microenvironment, the GO/TOBC hybrid matrix exhibited great potential to promote the growth of SGNs. The quantitative real-time PCR result confirmed that the GO/TOBC hydrogel can significantly accelerate the development of growth cones and filopodia, by increasing the mRNA expression levels of diap3, fscn2, and integrin β1 . These results suggest that GO/TOBC hydrogel scaffolds have the potential to be used to construct biomimetic nerve grafts for repairing or replacing nerve defects. Graphical abstract: Unlabelled Image